THE POWER OF THE UNSPOKEN: RUMOURS AND GOSSIPS IN THEIR EYES WERE WATCHING GOD AND TO KILL A MOCKINGBIRD - Sameeul Haq Nazki (INJOSEDU: International Journal of Social and Education, 2025)
This study explores the prevalence of gossip and rumours in Harper Lee’s To Kill a Mockingbird (1960) and Zora Neale Hurston’s Their Eyes Were Watching God (1937). Both novels demonstrate how unspoken words and hearsay impact the lives of heroes and bring a clash between them and their communities. Both are set in the American South during a period of social and racial conflict. This paper examines how Hurston and Lee employ whispers and gossip as narrative strategies to emphasise themes of prejudice, identity and societal judgement. In Hurston’s novel the unrelenting chatter of the villagers continuously impedes and shapes Janie Crawford’s path for self- discovery. It mirrors the social dynamics and power structures in her community as a challenge to her route of self-fulfillment. Analogously, Lee depicts the detrimental effects of racial and social prejudice in Maycomb, Alabama. He shows how the dissemination of false rumours affects the lives of people like Boo Radley. This study contends that rumours and gossip function as both representations of larger society issues and instruments for character development in both novels. The purpose of the article is to show how important rumours and gossip are to comprehending the writers’ criticisms of social injustice and the human condition. In the end, this analysis aims to highlight the significance of the unsaid and its deep influence on interpersonal relationships as well as community dynamics.